Ensuring the reliability and performance criterias of crankshafts - Kotliar, Alexey; Gasanov, Magomediemin; Basova, Yevheniia; Panamariova, Olga; Gubskyi, Sergii (Polish Technical Diagnostics Society, 2019)
The issues of efficiency improvement of manufacturing crankshafts in order to ensure their reliability and performance criteria are the priorities in modern production of internal combustion engines. Using the capabilities of modern special grinding machines can improve the quality of machining and obtain the necessary running characteristics of crankshafts. In work the questions connected with development of a method of calculation of rigidity of crankshafts for increase of accuracy of their machining, reliability and performance criteria’s are considered. Based on the proposed methodology, numerical calculations have performed and the possibility of determining the deflections and crankshafts rigidity in any section have been justified. The original construction of the following grinding steady rest for CNC grinding machines specified for machining the crankshaft main bearing journal and connecting rod journal is proposed. The construction design of the device allows for compensating the influence of the cutting force on the elastic strain of the part, depending on the change in its rigidity. The practical value of the research includes in develop recommendations for determining the optimal parameters for the round infeed grinding cycle of the crank pins from the point of view of productivity and accuracy.
Keywords: crankshaft; initial parameters method; reliability; grinding machine; rest